Odpowiedź:
Zad.1
a) 7a-⅓a a= 9
7*9-⅓*9 = 63-3=60
b) 3b²+2b b= -3
3*(-3)²+2*(-3) = 3*9+2*(-3) = 27+(-6)=21
c) (3x+4y)(6-x) x= 2 y= -3
18x-3x²+24y-4xy = 18*2-3*2²+24*(-3)-4*2*(-3) =
= 36-3*4+(-72)-8*(-3) = 36-12+(-72)+24 =
= 24+(-48) = (-24)
Zad.4
a) -4a+4+9a-2a = 3a+4
b) x-3y-4x+3y-2y = -3x-2y
c) 2x²+2y-5x-3y-x² = x²-y-5x
Zad.5
3x, x², 5, -2xy, -6y, 7
Nie jestem pewna czy tak ma być.
Zad.6
2a+3+3b+6a-3+7b+2 = 8a+2+10b
Zad.7
6ab = aby
-a²b² = -⅘a²b²
Wydaje mi się że jest dobrze, mam nadzieję, że pomogłam. :)